Evaluation of Cases Admitted for Age Determination to The Forensic Medicine Department of Akdeniz University School of Medicine - Atılgan, Mehmet; Akkoyun, Murat (The Bulletin of Legal Medicine, 2017)
Objective: Age determination is an important procedure which is frequently used in anthropologic studies and daily practice of forensic medicine for identification. In this study, in live cases, we aimed; to determine characteristics of age determination cases referred to Forensic Medicine Department of Akdeniz University School of Medicine between 2002 and 2011 to discuss findings of used method by comparing literature and to provide data about age determination in purpose to lead future studies will be conducted in our country. Materials and Methods: Birth places, gender, chronological age and claimed age, reported age, type of institution that requested an age determination, nature of event were all reviewed. We compared differences between reported ages and chronological ages. Results: In 10 years of study period, 205 age determination were carried out where 58 of them were male (28,3%) and 147 of them were female (71,7%). The average difference between determined ages and ID ages was 2,35 in cases between 0-22 years old. Where in sexual abuse/assault cases the average difference between determined ages and chronological ages were 2,21, the average for confirmed chronological age cases were 1,72. Conclusions: As a conclusion, there is statistically significant difference between chronological and determined ages. We proposed that instead of using methods suitable for other societies, a unique method should be formed for Turks via examining also tooth eruption and mineralization levels in a sufficient number of eligible samples selected from the country.